1996
DOI: 10.1007/bf00048532
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis and plant regeneration in cotyledonary explant cultures of Chinese cabbage

Abstract: Cotyledonary explants of Chinese cabbage were cultured on Murashige and Skoog's medium supplemented with various concentrations of 2,4-dichlorophenoxyacetic acid. Up to 20% of the cotyledonary explants produced somatic embryos with or without intervening callus production. Explants became more competent as the age of the source seedlings increased up to 8 days, but cotyledonary explants from 10-day-old seedlings were not responsive. Upon transfer to MS basal medium most of the somatic embryos developed into pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In addition to the gradient response of the hypocotyl segments, the age of the hypocotyls influenced the regenerative ability of perilla. The age of the cultured explants is believed to be a crucial regeneration factor in Geranium and Brassica species (Chang et al 1996;Choi et al 1996). However, this could be a kind of physiological age-related response.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to the gradient response of the hypocotyl segments, the age of the hypocotyls influenced the regenerative ability of perilla. The age of the cultured explants is believed to be a crucial regeneration factor in Geranium and Brassica species (Chang et al 1996;Choi et al 1996). However, this could be a kind of physiological age-related response.…”
Section: Discussionmentioning
confidence: 95%
“…Later on in 1979 he reported the feminized outgrowths on the stamen primordia of tobacco [25]. While establishing stamen cultures from its native explants it was found that growth rates are quite low, e.g., from all explants of Rosa hybrid only 14% of plants successfully produced stamen cultures whereas in Brassica campestris only 6.5% of regeneration was achieved [28,29]. Similarly, Lu and Enemata have studied the regeneration potential of sepals, stamens, and ovules from perianth explants of Hyacinthus orientalis L. in different developmental stages by means of exogenous hormones [26].…”
Section: Stamens Culturementioning
confidence: 99%
“…1) (Akmal et al 2011). In Chinese cabbage, somatic embryogenesis has been induced from cotyledonary explants (Choi et al 1996). Somatic embryos in cauliflower were obtained by Leroy (2000) using hypocotyl explants.…”
Section: Somatic Embryogenesismentioning
confidence: 99%
“…Regarding organogenesis, the genotype is a very important factor in the embryogenic frequency of most Brassica species. Only one of three different Chinese cabbage cultivars 'Top Salad' yielded somatic embryos (Choi et al 1996). Genotype effects are important in B. rapa (Baillie et al 1992), B. carinata (Barro and Martin 1999), and B. napus (Chuong et al 1988).…”
Section: Somatic Embryogenesismentioning
confidence: 99%